The Effect of Canva Application on Learning Interest and Critical Thinking of Elementary School Students - Badriyah, Lailatul; Tindangen, Makrina; Adji, Sandra Sukmaning (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2025)
The research is an experimental study of One Group Pretest-Posttest Design with a quantitative approach. The purpose of this study was to determine the effect of Canva application media on learning interest and critical thinking skills in science subjects at Elementary Schools Data analysis using simple linear regression analysis and multiple linear regression with the help of SPSS 22. The results of the multiple regression test found that the use of learning media based on the canva application had a simultaneous effect on interest in learning and critical thinking skills with atcount>ttablevalue of 3.640> 1.987, a significance level of 0.007. 1.987, the significance level is 0.000 < 0.05, the value ofFcount>Ftbelis 87.363> 3.95, and the Critical Thinking variableFcount>F table value is 65.122> 3.95, the significance level also shows 0.000 < 0.05. Therefore, based on hypothesis testing, it can be concluded that the use of canva application-based learning media on learning interest and critical thinking skills partially and simultaneously has a positive and significant effect.